Toward an Islamic Ethics of International Relations: A Research Agenda (American Journal of Islam and Society, 1993)
This study is an examination of the tole of ethical imperatives andconst&ts in the realm of international relations from the perspective ofclassical and modern Islamic theory. The study focuses upon three interrelatedquestions: (1) To what extent is an amoral conception of intemationalpolitics possible within an Islamic framework? (2) To what extentis classical and/or modem Islamic theory compatible with the contemporaryintemational system based upon the sovereign, independent nationstate?(3) What are the ramifications of Muslim accommodations with thetheory of the sovereign nation-state in the aEas of just war, nuclear deterrence,and distributive justice?The historical development of Islamic thought and contemporaryMuslim perspectives will be compared with the historical development ofWestern theories and contemporary Western perspectives on the tole ofethics in international relations. The purpose of this thesis is both toevaluate critically classical and contemporary Islamic perspectives onintemational relations and to develop systematically an Islamic ethicalframework for issues still largely neglected by modem Muslim theorists:just war, the morality of nuclear detemce, and distributive justice.Theoretical ArgumentIs ethical theory applicable in the realm of international relations? Ifso, what role does or should it play in the conduct of foreign policy?The late international relations theorist Hedley Bull suggests h ephilosophical strands in Western conceptions of intemational relations.'Each is to some extent both descriptive as well as prescriptive. Each providesdifferent answers to the questions above. (1) The Hobbesian or"realist" paradigm views international relations as a state of natm dominatedby independent, self-reliant states struggling for power and prestigein a milieu inimical to cooperation and devoid of international norms ormomlity. (2) The Grotian or "internationalist" tradition views intemationalElations as the arena of sovereign states, but acting in a milieu characterizedby pervasive interdependence in economic, military, legal, andpolitical concerns. The possibility of ethical considerations is stronger inthis environment since a rudimentary international society of commonvalues, interests, and institutions does exist. (3) The Kantian or ...